KOREKSI UJIAN ESSAY OTOMATIS DENGAN TEXT MINING PADA E-LEARNING STIKOM BALI - Ida Bagus Ketut Surya Arnawa (Jurnal Teknologi Informasi dan Komputer, 2019)
ABSTRACTOne of the most important things in the world of education is evaluation in the learning process. The purpose of conducting an evaluation process is to find out the extent to which students understanding a material that has been delivered. There are several ways that can be done in conducting an evaluation, one of them is by giving exam questions to measure students' abilities. STIKOM Bali has implemented online evaluation through e-learning system. The evaluation model developed in the form of essay exam questions where students are asked to input answers to each question. But in its implementation the lecturer is still experiencing difficulties and requires more time in correcting the answers to the exam questions. This can affect the decline in objectivity in the assessment. The efforts that need to be made to overcome these problems need to be developed techniques that can automatically correct the results of essay exams using the Rabin Karp algorithm. The results obtained from the development of automatic correction techniques using the Rabin Karp algorithm are that they have succeeded in making automatic corrections to the results of the essay exam by matching the answers of students with the answer key using parsing-gram and hashing. The final score of the essay exam is a number from 1 to 100.Keywords: Rabin-Karp, automatic correction, essay.ABSTRAKSalah satu hal yang terpenting dalam dunia pendidikan adalah evaluasi dalam proses pembelajaran. Adapun tujuan melakukan proses evaluasi adalah untuk mengetahui sejauh mana pemahaman mahasiswa dalam menyerap/memahami suatu materi yang telah disampaikan. Ada beberapa cara yang dapat dilakukan dalam melakukan evaluasi salah satunya dengan memberikan soal ujian guna untuk mengukur kemampuan mahasiswa. STIKOM Bali sudah menerapkan evaluasi online melalui sistem e-learning. Model evaluasi yang dikembangkan berupa soal ujian essay dimana mahasiswa diminta menginputkan jawaban pada masing-masing soal. Namun dalam implementasinya dosen masih mengalami kesulitan dan membutuhkan waktu yang lebih dalam melakukan koreksi jawaban dari soal ujian. Hal ini dapat mempengaruhi penurunan objektifitas dalam penilaian. Adapun upaya yang perlu dilakukan untuk menanggulangi permasalan tersebut perlu dikembangkan teknik yang dapat mengkoreksi otomatis hasil ujian essay dengan menggunakan algoritma Rabin Karp. Hasil yang didapat dari pengembangan teknik koreksi otomatis menggunakan algoritma Rabin Karp yaitu sudah berhasil melakuakan koreksi secara otomatis hasil ujian essay dengan cara mencocokan jawaban mahasiswa dengan kunci jawaban menggunakan parsing -gram dan hashing. Nilai akhir dari penilaian ujian essay berupa angka dari 1 sampai 100.Kata Kunci : Rabin-Karp, koreksi otomatis,essay.